MODEL NON LINEAR PENYAKIT DIABETES - Aminah Ekawati; Lina Aryati (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2011)
The mathematical model may be classified by non-linear. The non-linear case is discussedand the critical values of the population are analyzed for stability. Numerical methods aredeveloped for solving the model equations.